Risk ratio of Delirium in crIticaly ill patient using the Confusion Assessment Method for Intensive Care Unit during admission from October to Desember 2015 in Intensive Care Unit Dr. Hasan Sadikin Hospital - Rohmawanur, Tubagus Yuli; , Indriasari; Redjeki, Ike Sri (Majalah Anestesia dan Critical Care, 2015)
Delirium is an acute and fluctuative state marked by changes in mental, concioussness, attention, cognitive and perspective which develops within a certain time frame (usually hours to days). Delirium has a high incident on criticaly ill patients. The aim of this research is to investigate risk ratio (RR) of delirium in criticaly ill scored by the confusion assessment methode for the intensive care unit ( CAM-ICU) during admission in general intensive care unit (GICU) Hasan Sadikin Hospital. This is an observational analytic study with prospective cohort on 91 patients during 24 hours of GICU care from October to December 2015. Statistical analysis was done with chi square test which measures the percentage and RR of delirium.The result is the incidence of delirium in Hasan Sadikin Hospital GICU was 27.9 %. Analysis shows that there is a significant relationship between delirium with RR >1 to delirium based on sedation history is 3.16, ventilated patients was 2.37, electrolyrte imbalance 2.37, infectious disease 2.13, comorbid 1.86, neurological disorder 1.622, and analysis shows that there is a significant relationship between delirium delirium and history of sedation, electrolyte imbalance and ventilated patients with p value <0,05. The conclussion of this study is that the incidence of delirium in Dr. Hasan Sadikin Hospital GICU has a higher incidence on critically ill patient with risk factors involved. Highest risk factor is sedation history which increases the risk by 3.16 times more.